Comparative analysis of the functional state of the microcirculation of the prosthetic bed in patients with complete adentia after Covid-19 disease - Khabilov N.L; Shzaripov S.S; Inoyatov A.Sh (Genius Journals, 2022)
The outbreak of the new coronavirus infection SARS- CoV-19 has become a serious test for the global health system. Within a short time, research began on the etiology, pathogenesis and treatment possibilities of a new viral disease. Current definitions of Covid-19 cases depend solely on typical pulmonary symptoms [1- 7, 11-14] common with other respiratory diseases. Meanwhile, from a laboratory point of view, leukopenia with lymphopenia, thrombocytopenia, high values of C-reactive proteins and low levels of procalcitonin are well-established diagnostic indicators [23]. In addition, many symptoms manifest themselves in the oral cavity [26-28]. The most frequent lesions in descending order were tongue (38%), lip mucosa (26%), palate (22%), gum (8%), cheek mucosa (5%), oropharynx (4%) and tonsils. (1%). The proposed diagnoses of lesions included aphthous stomatitis, herpetiform lesions, candidiasis, vasculitis, Kawasaki type, mucositis, and drug rash, necrotizing periodontal disease, angular cheilitis, atypical Sweet syndrome and Melkerson-Rosenthal syndrome. Lesions of the oral cavity were symptomatic (soreness, burning or itching) in 68% of cases. Oral lesions were almost the same in both sexes (49% of women, 51% of men). The delay time between the appearance of systemic symptoms and oral cavity lesions ranged from 4 days before and up to 12 weeks after the appearance of systemic symptoms. In 3% of cases, oral lesions preceded systemic symptoms, and in 4% of cases, oral and systemic symptoms were simultaneously manifested. The longest latency period was for lesions like Kawasaki syndrome. Oral lesions healed from three to 28 days after their appearance. Various types of therapy were prescribed for oral lesions, including chlorhexidine mouthwash, nystatin, oral fluconazole, local or systemic corticosteroids, systemic antibiotics, systemic acyclovir, artificial saliva and photobiomodulation therapy, depending on the etiology [16-19, 20-22, 24, 26]. According to researchers, patients with Covid-19 often have thrombotic complications with the detection of large blood clots and signs of thrombosis at the microcirculatory level. This is due to several pathogenetic mechanisms at once. A sharp decrease in the ability of red blood cells to change their shape during the passage of vessels of the microcirculatory bed with a diameter smaller than the diameter of the red blood cell was also revealed [15, 22]. But in dentistry, there is still no clear data on whether Covid-19 is the direct cause of microcirculation disorders in the tissues of the oral mucosa that lead to inflammatory periodontal diseases. The screening capabilities of the method of high-frequency ultrasound Dopplerography in the study of microcirculation of the oral mucosa in Covid19 disease are also unclear.
Keywords: SARS- CoV-19; Covid-19; dentistry; oral cavity